Gene expression changes in blastocyst hatching affect embryo implantation success in mice - Liyou An; Liang Zhang; Yulin Wu; Yadi Teng; Zihan Liu; Meixiang Ma; Miaolong Li; Xinrong Peng; Chenxi Liu (Frontiers in Cell and Developmental Biology)
In mammalian embryonic development, blastocyst hatching is essential for normal implantation and development of the fetus. We reported previously that blastocysts hatching out of the zona pellucida (ZP) exhibited site preferences that were associated with pregnancy outcomes. To characterize these site differences, we analyzed the transcriptomes in the following developing mouse blastocysts within 16 h of hatching: expanding (E), hatching from the A-site (A), B-site (B), and C-site (C), hatched (H), and non-hatching (N). By principal component analysis and hierarchical cluster analysis, we determined that the gene expression profiles of A and B blastocysts, which resulted in good fertility, clustered closely. C and N blastocysts, which resulted in poor fertility, clustered closely, but distantly from A and B. Embryos hatched at B- vs. C-sites, with good vs. poor pregnancy, showed 178 differentially expressed genes (DEGs), mainly involved in immunity, which correlated positively with birth rate. These DEGs were primarily regulated by transcription factors TCF24 and DLX3. During blastocyst hatching, immune-related genes were regulated, such as Ptgs1, Lyz2, Il-α, Cfb (upregulated) and Cd36 (downregulated). By immunofluorescence staining, we found C3 and IL-1β on the extra-luminal surface of the trophectoderm of the hatched blastocyst, suggesting that they play a role in maternal-fetal interactions. As the blastocysts developed from the expanding to the fully hatched state, 307 DEGs were either upregulated by transcription factor ATOH8 or downregulated by SPIC to switch on immune pathways. Based on the hatching outcome, we identified three transcription patterns in developing blastocysts, with complex changes in the transcriptional regulation network of failed hatched blastocysts vs. successfully hatched blastocysts. We developed a LASSO regression-based model using DEGs Lyz2, Cd36, Cfb, and Cyp17a1 to predict implantation success. This study revealed the diverse, multidimensional developmental fates of blastocysts during short-term hatching and indicated that the immune properties of the embryo had a major effect on blastocyst hatching outcomes. We suggest that transcriptional changes and their regulation during the development of the preimplantation blastocyst affect implantation. This study contributes to our understanding of the role of transcriptional changes in mammalian embryonic development during hatching and their effect on maternal-fetal interactions.